Extraction solvents in microalgal lipid extraction for biofuel production: A review [Pelarut pengekstrakan dalam pengekstrakan lipid mikroalgal untuk penghasilan bahan api bio: satu tinjauan] - Hwang T.Y.; Kin C.M.; Shing W.L. (Malaysian Society of Analytical Sciences, 2023)
Oleaginous microalgae biomass has gained noteworthy attention as feedstock for biofuel production due to its fast growth rate and capability of growing in non-arable land with high lipid content. Among biofuels, biodiesel has been a prevailing area of interest to many researchers. Prior to transformation of microalgae lipid into biodiesel, a lipid extraction step needs to be performed to disrupt the microalgal cell walls in order to extract the lipid. Hence, selecting an appropriate extraction solvent is of the utmost importance to ensure the efficient extraction of desired lipid content which can then be transformed into high quality biodiesel. Conventional organic solvents such as chloroform, dichloromethane and methanol are usually used in lipid extraction due to its high extraction efficiency. However, toxicity and environmental issues related to these solvents are of major concerns. Hence, many recent studies have focused on the use of green solvents such as bio-based solvents, supercritical carbon dioxide and ionic liquids. This review discusses the use of conventional organic solvents and green solvents in microalgae lipid extraction. Advantages and shortcomings of these solvents are also discussed. In addition, the future perspective for extraction solvents used in lipid extraction is also discussed. 2021, Malaysian Society of Analytical Sciences. All rights reserved.